Bílá růže: Odboj studentů za Třetí říše - Šindelářová, Lenka (Lidé města, 2006)
Bílá růže is a name of group of people who had the courage, only few people had, to oppose Hitler and National Socialism ideology of the Third Reich. In many respects, their resistance is singular and extraordinary, which should be – when judging their deeds – taken into account, unconditionally. The first actions of Bílá růže date back to summer of 1942. It was a period when Germany was at the height of its glory. Almost the entire Europe was under its dominance and the German Army celebrated unprecedented successes also in northern Africa and in the Atlantic Ocean. Of course, the population was informed about it and only few resisted enthusiasm and optimistic expectations about the future. During that period, majority of the German nation still infinitely believed in Hitler’s victory of the war and wished for it. Activities of Bílá růže took place primarily in Munich, i.e. in a city where NSDAP was founded in 1920, where the unsuccessful Hitler’s putsch took place three years later, and where the Party and its leader later had their official seat. Munich was the cradle of National Socialism, the fact crowned by Hitler in 1935 by awarding the city title of the “Capital City of the Movement”. Moreover, this resistance originated in the university environment, despite the fact that since 1934 the university was under administration of the Reich ministry and as an institution represented the Nazi state, faithfully. Close and wider circle of Bílá růže was composed of young people, almost exclusively. People whom Hitler and the Party trusted the most and expected the most from. Significant part of their life was spent under the Nazi propaganda, impacting their education. To escape its influence was a very difficult task. Moreover, these people were not directly under threat; people whose resistance did stem primarily from their conscience and thus bearing, most of all, moral legacy. Their resistance can not be categorized as purely political, military or religious one. Their principal motive was their demand for freedom and to establish such living conditions where one is not forced to act in contradiction with one’s own conscience.